Polarization Gratings Spontaneously Formed from a Helical Twist‐Bend Nematic Phase. Issue 19 (27th June 2018) - Vaupotič, Nataša; Ali, Muhammad; Majewski, Paweł W.; Gorecka, Ewa; Pociecha, Damian
Abstract: Spontaneous formation of polarization gratings by liquid crystalline phase made of bent dimeric molecules is reported. The grating is formed within the temperature range of the twist bend modulated nematic phase, NTB, without the necessity to pattern the cell surfaces, therefore the modulated nematic phase is a promising candidate for low‐cost modulators and beam steering devices, the polarization properties of which depend on temperature. In addition, the study of the diffracted light properties turns out to be a sensitive measuring technique for determination of the 3D spatial variation of the optic axis in the cell. Abstract : Spontaneous grating : Undulations of the heliconical axis in thin cells of the twist‐bend modulated nematic phase act as a polarization diffraction grating, which is formed spontaneously without surface patterning. Polarization studies of the diffracted beams serve as an inexpensive and reliable measuring technique to determine spatial variation of the heliconical axis.